SSACC -SERVIÇO DE SEGURANÇA PARA AUTENTICAÇÃO CIENTE DO CONTEXTO: para Dispositivos Móveis no Paradigma da Computação em Nuvem - MORAES, Renato Ubaldo Moreira e (2014)
Nowadays, there was a massive inclusion of smart mobile devices, known as smartphones, and with this accession, there s consequently a large increase in the consumption of information, especially from the internet. To support the great demand for information access, it s created a numerous devices to facilitate both access, the creation and the storage of such information, among the best known and disseminated currently is cloud computing. The feedback takes currently, an increasingly important and even critical for some entities, size and value turns out to be very desirable. Being often target capture and espionage attempts. To obtain data confidential information hackers use numerous devices, and more is used to scan networks. In other words can be described as scan "Scans notifications in computer networks, in order to identify which computers are active and which services are available for them. It is widely used by attackers to identify potential targets because it allows associate potential vulnerabilities to services enabled on a computer " [10]. According to [10] the number of attacks has been widening each year as shown in Figure 1.1 and 1.2 which are in section 1.1. Based on this high number incidents, the growth of the information consumer by means of devices furniture and the need to improve energy costs, the proposed establishment of the Office Security for Context Aware of authentication (Serviço de Segurança para Autenticação Ciente do Contexto(SSACC)) is required for today. The ssacc focus to provide a secure channel for transfer files to a server, using context information and reducing energy waste, thus saving resources and framing the Green Computing. Made based on the Secure Socket Layer (SSL), which is a widely used protocol that provides secure communication through a network. It uses several different cryptographic processes to ensure that data sent through the network is secure. It provides a security enhancement for the Transport Control Protocol (TCP) / Internet Protocol (IP) standard, which is used for communication with the Internet. SSL uses public key cryptography to provide authentication. The SSL protocol also uses encryption of the private key and digital signatures to ensure privacy and the integrity of data " [26].